2018
DOI: 10.1038/s41598-018-19488-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Friction Characteristics of Metallic Glass Composites at the Microstructural Length-scales

Abstract: Metallic glass composites represent a unique alloy design strategy comprising of in situ crystalline dendrites in an amorphous matrix to achieve damage tolerance unseen in conventional structural materials. They are promising for a range of advanced applications including spacecraft gears, high-performance sporting goods and bio-implants, all of which demand high surface degradation resistance. Here, we evaluated the phase-specific electrochemical and friction characteristics of a Zr-based metallic glass compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The correlation between corrosion potential and work function investigated for crystalline 32 and amorphous 33 materials show that metallic alloys with higher work function typically show better corrosion resistance due to lower electropositivity. 34 In other words, corrosion is affected by the Fig. 8 a Low magnification SEM image of E-HEA after polarization test in 3.5 wt.% NaCl solution; b high magnification SEM image corresponding to the black box in the previous image showing preferential dissolution of B2 phase; c pitting in the corroded sample with pit initiation in the region with high B2 phase fraction surface electron behavior or electron activity, which may be characterized by work function.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation between corrosion potential and work function investigated for crystalline 32 and amorphous 33 materials show that metallic alloys with higher work function typically show better corrosion resistance due to lower electropositivity. 34 In other words, corrosion is affected by the Fig. 8 a Low magnification SEM image of E-HEA after polarization test in 3.5 wt.% NaCl solution; b high magnification SEM image corresponding to the black box in the previous image showing preferential dissolution of B2 phase; c pitting in the corroded sample with pit initiation in the region with high B2 phase fraction surface electron behavior or electron activity, which may be characterized by work function.…”
Section: Resultsmentioning
confidence: 99%
“…Higher adhesion for metal-on-metal wear has been reported for more electropositive alloys. 34 Buckley's hypothesis 37 suggests that chemically active metals (i.e., electron donors) are prone to strong adhesion as opposed to inert metals. 38 Therefore, it can be concluded that the more electropositive nature of B2 phase might have resulted in a stronger adhesion to the cube-corner indenter and resulted in higher localized stresses (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is paramount to investigate and understand the electrochemical response during mechanochemical degradation in vivo under dynamic loading. In terms of design and development of new metallic biomaterials, a new generation of biocompatible alloys named high‐entropy alloys (HEAs) and bulk metallic glasses (BMG) show excellent mechanical and corrosion behaviour that is superior in many cases compared to presently used bioimplant materials (A. Ayyagari, Hasannaeimi, Arora, Hasannaeimi, Arora, & Mukherjee, 2018; A. Ayyagari, Hasannaeimi, Grewal, et al., 2018; Ren et al., 2019; Todai et al., 2017). HEAs are composed of multiple principal elements that result in unique strengthening mechanisms and resistance to failure under dynamic loading.…”
Section: Electrochemical Measurements Sensors and Degradation Mechanmentioning
confidence: 99%
“…This may be of interest in tribology for developing super-lubricity complex composition coatings. Phase-specific friction studies will provide significant insights into surface degradation from multi-body wear in multi-phase CCAs [101]. Ni free complex alloys might be attractive for biomedical applications.…”
Section: Future Opportunities and Outlookmentioning
confidence: 99%